Monochromatic X-ray sources based on a mechanism of real and virtual photon diffraction in crystals; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 266, iss. 17 - Wagner A. R. Aleksandr Rudolfovich; Kuznetsov S. I. Sergey Ivanovich; Potylitsyn A. P. Alexander Petrovich; Razin S. V.; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich (2008, 2008)
Title screen